(untitled) (Community Based Medical Journal, 2022)
Decision making in healthcare does not depend only on mastery of knowledge, clinical skills, and technical competencies, rather it is largely influenced by ethical competences of the physicians. Teaching medical ethics in undergraduate medical education (MBBS programme in Bangladesh) helps medical students recognize the importance of being sensitive to ethical issues within everyday clinical practice and develop in them the ability to effectively address the concerns of patients and families, as well as participants in health research and larger society. In medical practice, its ethical component is treated as an obligatory one, no matter what the specialty is. The importance of ethics in medicine is increasing greatly day by day; its dimensions are also changing. In this review paper, we have tried to discuss some effective changes in medical ethics curriculum, methods of teaching and learning, faculty development, and institutional culture. All stakeholders should think about it and take necessary actions into that direction, which will ultimately lead to building a more ethical, more patient-centred, more professional medical community in the country. CBMJ 2022 July: vol. 11 no. 02 P: 167-175